Parametric Numerical Study on Flexural Behaviour of Cold-Formed Steel Channel Sections: Effects of Lip, Flange Width, and Thickness - Pavan Tikate; Ishwar Sonar (The Bioscan, 2026)
This paper presents a detailed numerical investigation on the flexural behaviour of cold-formed steel (CFS) channel sections with a focus on three critical geometric parameters: lip provision, flange width, and section thickness. The study aims to evaluate how these parameters influence the flexural capacity, stiffness, and overall performance of CFS members under loading. A series of channel configurations were modelled and analyzed using STAAD Pro under single-point load condition, replicating typical bending scenarios in real structures. Each configuration was examined for its load-deflection response, critical buckling behaviour, and capacity enhancement relative to standard design benchmarks outlined in IS 801:1975. The study concludes that lipped sections significantly outperform unlipped ones in terms of stiffness and stability. Additionally, increased thickness and wider flanges provide notable gains in load capacity and serviceability performance. The study provides a foundation for future development of composite systems involving CFS sections and additional reinforcements to mitigate identified structural weaknesses. Keywords Cold-formed steel, Channel sections, Flexural behavior, Lip provision, Flange width, Section thickness, STAAD Pro, Structural performance.